(untitled) (Feni University Journal, 2026)
The present-day land administration of Bangladesh is the result of thousands of years of legal and administrative evolution. And the history testifies rega rding the misery of the minority groups of this land. Irrespective of ethnic and religious identity, the minority people were victims of land grabbing by the majority and that is without any legal remedy. Although, law is supposed to provide protection to the citizens from any illegal actions but in the case of minority land rights, the reality totally prescribes the opposite. In Bangladesh, religious minorities have been tagged as ‘enemy’ and their lands have been grabbed in the name of ‘enemy property’, a phenomenon that can be regarded as a gross violation of human rights. Although, subsequent legal developments were made to return the grabbed lands, but the field reality raises the question of political goodwill to really implement such laws. Again, the ongoing land grabbing through misuse of law and through illegal ways has posed a threat to the peace and stability of the country. The minority is active in protest for their right, but their voices are being suppressed by the deep-rooted evil enterprise in the country. But if effective legal reforms are taken to mitigate such legal barriers, the situation is bound to improve. But to bring forth such reforms the political goodwill is a must. Without such goodwill, the misery of the minority would come around in circles just like it did in the past. FENI UNIVERSITY JOURNAL, 2025, 4(1), PP. (107-132)